Fibrous epulis associated with impacted lower right third molar - Ni Putu Mira Sumarta; David B Kamadjaja (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Epulis or epulides are lesions associated with gingival tissues. Fibrous epulis is a type of hyperplastic fibrous tissue mass located at the gingival which is slow growing, painless, having same color as the oral mucosa and firm on palpation. Anterior regions of the oral cavity are the frequently affected sites as these areas are more prone to be affected by calculus deposition and poor plaque control due to frequent teeth malposition. Removal of any irritating factors and excision of the lesion are the usual treatments. Purpose: This case report presents a rare case of fibrous epulis which occurred in the posterior region of the oral cavity and associated with impacted lower third molar. Case: A case of fibrous epulis at the lower right third molar area of three months duration is presented. The mass was slow growing, painless and on examination it was a pedunculated mass overlying the unerupted lower right third molar, having same color with the oral mucosa and firm on palpation. Clinically, the lesion was diagnosed as fibrous epulis associated with impacted lower right third molar. Case management: The treatment were surgical excision of the epulis and removal of the lower right third molar. The histopathology result showed tissue with squamous epithelial lining, achanthotic fibrous connective tissue, mononuclear inflammatory cells and few capillaries without signs of malignancy. This is consistent with the diagnosis of fibrous epulis. Conclusion: Fibrous epulis, although frequently occurred at the anterior region of the oral cavity, may rarely grow at the area of lower third molar. This phenomenon supports the theory that epulis can grow on any surface of oral mucous membrane as long as local irritants are present.